PRINSIP DAN NORMA HUKUM PENGADAAN BARANG/JASA SECARA SWAKELOLA - Sarah Selfina Kuahaty (SASI, 2010)
Procurement of goods/services the government is a government activity that has generally been regulated in Presidential Regulation Number 54 Year 2010 Concerning the Procurement of Goods/services of the Government. Procurement conducted by the government can be implemented by using a provider of goods/services or self-managed. In the procurement of goods/services are self-managed, then the planned procurement of work, work, and supervised solely by implementing self-management, among others can be done by the Ministry / Institution / Work Unit Regional / Other Institutions and Community Group. In the implementation of procurement of goods/services should be based on the principle of self-managed Efficient, Effective, Transparent, Open, Competitive, Fair / non-discriminatory, and Accountable. In the procurement of goods/services in self-management is also inseparable from the making of the contract, then in addition to these principles are self-managed procurement should also be implemented based on the principles as set forth in Civil Code principle of freedom of contract, Consensualism Principles, Principle of equality of the parties, Principles Pacta sunt servanda, and the Principles of good faith